A Framework for 5G and Beyond, Non-Terrestrial Networks, and V2X - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Würzburg Workshop on 6G Networks (WueWoWAS’24), 2024)
The integration of 5G and beyond Non-Terrestrial Networks with vehicular applications addresses critical challenges, such as ensuring ultra-reliable low-latency communication (URLLC) and supporting enhanced mobile broadband (eMBB) services. This convergence is expected to improve road safety, traffic efficiency, and enable advanced autonomous driving capabilities. In this paper we aim to provide a first overview of the evaluation results in the context of vehicle to everything (V2X

An ns-3 model for multipath communication with terrestrial and satellite links - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
Some terrestrial Internet access links provide only low data rates. Internet access via geostationary satellites on the other hand provides data rates of up to 50 Mbit/s, but suffers from high latencies. The combination of low data rate, low latency Internet access (e.g., DSL light) and high data rate, high latency Internet access (e.g., geostationary satellites) can utilize the advantages of both. We discuss multipath communication architectures and scheduling strategies for such heterogeneous link combinations. The solution described in this paper relies on Split TCP and Performance Enhancement Proxies. We implement and evaluate the solution with the network simulator ns-3. A well-established traffic model for loading websites is enhanced with different HTTP variants. The results show that the combination of heterogeneous link types can result in page load times close to as if there was a high data rate, low latency Internet access.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Hybrid access; Multipath communication; Network simulation; Terrestrial and satellite networks

A Power Line Communication Topology Module for ns–3 and DCE - Gäde, Bernhard; Lehmann, Andreas; Deutschmann, Jörg; Huber, Johannes (Smart Grid Communications (SmartGridComm), 2017 IEEE International Conference on, 2017)
Protocol development for power line communications (PLC) relies heavily on testing and verification under various conditions. As it is very difficult to implement testbeds with large and flexible topologies, network simulation is usually the means of choice. It is of particular importance that the physical layer model is not only flexible and of limited complexity, but also provides a good degree of realism. Especially for PLC the topology has large impact. We introduce a new module for the simulation of PLC networks with network simulator 3 (ns-3) and Direct Code Execution (DCE) that is flexible and efficient but also offers accurate results. We present a detailed description of the module, its features and implementation. We provide a comparison with the output of the circuit simulator LTspice for verification.

Broadband Internet Access via Satellite: Performance Measurements with different Operators and Applications - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Breitbandversorgung in Deutschland - 16. ITG-Fachkonferenz, 2022)

Broadband Internet access via satellite: State-of-the-art and future directions - Deutschmann, Jörg; Heyn, Thomas; Rohde, Christian; Hielscher, Kai-Steffen; German, Reinhard (Breitbandversorgung in Deutschland - 15. ITG-Fachkonferenz, 2021)
Modern communication satellites provide high data rates and area-wide coverage, making them suitable for broadband Internet access. This paper gives an overview of state-of-the-art satellite networks, including a discussion about geostationary high-latency satellite links and the negative implications for Internet protocols. Moreover, current developments and future systems are reviewed: hybrid access with satellite and terrestrial networks, upcoming satellite systems in low and medium Earth orbit, and standardization activities regarding 5G non-terrestrial networks and DVB-S2X physical layer techniques such as beam-hopping and MIMO.
CRIS-Team Scopus Importer:2021-11-05

Careful Resume: Design and Analysis with Picoquic over Satellite Paths - Hofstätter, Matthias; Deutschmann, Jörg; Secchi, Raffaello; Fairhurst, Gorry; German, Reinhard (2025 12th Advanced Satellite Multimedia Systems Conference and the 18th Signal Processing for Space Communications Workshop (ASMS/SPSC), 2025)
Slow Start increases the congestion window by doubling each round trip until congestion is detected. As a result, reaching optimal speed typically takes several round trip times, especially important in high bandwidth-delay product networks. Geostationary satellite communications now use Performance Enhancing Proxies to accelerate the growth of the congestion window. However, these are ineffective for connections with encrypted headers or UDP traffic. We propose a new method, Careful Resume, that enables a rapid ramp-up of congestion control by reusing previous parameters. We implement Careful Resume in Picoquic and run performance tests using an emulated geostationary satellite path, three real geostationary satellite networks, the low Earth orbit satellite megaconstellation Starlink, and a cellular 5G network. Results confirm that Careful Resume accelerates the ramp-up process, reducing total transmission time. Even for connections with lower bandwidth-delay products, the network congestion point can be reached much more quickly. Benefits are particularly pronounced for paths with high bandwidth-delay products and medium-sized transfers such as web traffi
Keywords: Careful Resume; Congestion Control; Transport Protocol; QUIC; Slow Start

Crowdsourced Starlink Performance Measurements from https://starlinkstatus.space - Bülo, Manuel; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (ICC 2024 - IEEE International Conference on Communications, 2024)
Starlink is the largest and most powerful low Earth orbit satellite megaconstellation built to date. Since its debut in 2021, there has been an enormous interest in performance evaluations. https://starlinkstatus.space is a crowdsourced measurement platform based on the Ookla speed test. This paper presents its design, user statistics, and results: Almost 1.7 million measurements from 309 users and 29 countries. The median goodput rates are between 100 Mbit/s and 200 Mbit/s in the forward link (download), and between 10 Mbit/s and 20 Mbit/s in the return link (upload). Goodput rates in North America are lower than in other countries, and the time of day matters, with peak time performance down to a median of 50 Mbit/s. Median round trip times are between 40 ms and 50 ms. Latency under load seems to have improved recently. The hardware version of the standard user terminal does not seem to have an impact on the performance.<br

CUBIC Local Loss Recovery vs. BBR on (Satellite) Internet Paths - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IEEE Workshop on Local and Metropolitan Area Networks, 2023)
Paths with high delay and packet loss are problematic for transport protocols, especially when loss-based congestion control algorithms are used. Our topology of interest is a geostationary satellite path (round trip time approx. 600 ms) with additional packet loss, which could be caused by a lossy wireless local area network. In geostationary satellite networks, Performance Enhancing Proxies split TCP connections to improve performance, but this is not possible in case of encrypted transport protocols (VPNs, QUIC). This motivates the use of local loss recovery, i.e., avoiding packet loss on specific path segments. We briefly discuss related concepts, architectures, and protocols. We then evaluate local loss recovery using a TCP tunnel on the lossy link. By means of a simple emulation setup, we demonstrate that local loss recovery has great performance benefits if CUBIC is used. It is also shown that BBR works well for high-delay and lossy paths even without local loss recovery.
CRIS-Team Scopus Importer:2023-08-25
Keywords: congestion control; local loss recovery; performance enhancing proxies

Internet via Satellite: GEO vs. LEO, OpenVPN vs. Wireguard, and CUBIC vs. BBR - Deutschmann, Jörg; Jahandar, Saeid; Hielscher, Kai-Steffen; German, Reinhard (Proceedings of the 1st ACM MobiCom Workshop on Satellite Networking and Computing, 2023)
Geostationary (GEO) satellite communication achieves high data rates but relies on Performance Enhancing Proxies to mitigate the negative effects of high latency paths. However, such proxies cannot be applied if the transport protocol headers are encrypted, as is the case for VPNs. Recently, there has been an enormous momentum towards low Earth orbit megaconstellations, with Starlink currently being the largest satellite constellation ever deployed. In this paper, we compare two GEO systems with the Starlink megaconstallation, and unencrypted TCP with two different VPN networks: OpenVPN and Wireguard. The impact of congestion control algorithms is shown by a comparison of BBR and CUBIC. Traffic generation is done with TCP bulk data transfers. Results confirm that GEO systems achieve their configured link rate if PEPs can be applied. Without PEPs, the convergence towards the path capacity takes a considerable amount of time ( 10 s) and goodput of a single flow is limited ( 30 Mbit/s) due to default buffer sizes. Starlink achieves high data rates ( 200 Mbit/s in forward link, 25 Mbit/s in return link), and compared to GEO systems, has much lower latencies. Wireguard usually performs better than OpenVPN, and BBR usually performs better than CUBIC. A non-optimal combination is Starlink with OpenVPN and CUBIC, which reaches a goodput of only 50 Mbit/s for a single flow in the forward link. <br

Multipath Communication over Terrestrial and Satellite Links - Deutschmann, Jörg; Hielscher, Kai-Steffen; Keil, Torben; German, Reinhard (2018)
Multipath communication with heterogeneous channels is very challenging. In this paper, we describe the combination of terrestrial and satellite internet access links. We review related concepts for such a setup (MPTCP, CMT-SCTP, MPQUIC, Layer 3 Bonding). We propose that dynamically switching a single flow among heterogeneous communication links is a simple and efficient scheduling strategy. Finally, architectures and protocols (MOBIKE, PMIPv6, LISP) are discussed regarding their eligibility for multipath communication and heterogeneous link bonding.

Network Simulation for Powerline Protocols with Direct Code Execution Applied to DLC (R)-3000 SFN - Deutschmann, Jörg; Lehmann, Andreas; Hampel, Johannes; Huber, Johannes (2014)
The simulation of powerline communication (PLC) networks with larger numbers of nodes and with different channel conditions is essential for the development of the respective protocols, especially regarding medium access and network layer strategies. However, creating realistic models for network simulations is a complex process and demands high resources. Therefore, emulation and testbeds have been a necessary addition for testing and verification. In this paper, we propose a solution that brings both approaches closer together. Via the direct code execution (DCE) framework of the network simulator 3 (ns-3) project, we show how the machine code from real devices can be run within the network simulator, thus making it unnecessary to model the PLC protocol in another instance, namely the simulator. We will show results for the DLC (R)-3000 Single Frequency Network (SFN) PLC protocol and a proof of concept, that the same code performs on real PLC devices as well as within the simulator.

One-Way Delay and Goodput Measurements with a VDSL, DOCSIS, and MPTCP Internet Access - Ammon, Lorenz; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2020 43rd International Conference on Telecommunications and Signal Processing, TSP 2020, 2020)
Different Internet access technologies have both advantages and disadvantages. Two common wire-based standards are Very high speed Digital Subscriber Line (VDSL) and Data Over Cable Service Interface Specification (DOCSIS). The simultaneous use of multiple Internet access links can be achieved with Multipath TCP (MPTCP). This paper presents one-way delay and bulk data transfer measurements of a typical end-user DSL as well as DOCSIS Internet access. In addition, MPTCP is used for bandwidth aggregation of both Internet access links. The results show that the DSL Internet access has a more stable performance than the DOCSIS Internet access. MPTCP can provide bandwidth aggregation unless the link rates are too different. The observed fluctuations indicate that Internet access link models with simple impairment assumptions need to be extended. However, some effects cannot be explained without having access to the operator and backbone infrastructure.
CRIS-Team Scopus Importer:2020-09-18
Keywords: DOCSIS; Goodput; Hybrid Access; Multipath TCP; Network Measurements; One-Way Delay; Throughput; VDSL

Performance Evaluation of ns-3 Real-Time Emulation - Ottens, Martin; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IEEE Access, 2025)
With its real-time mode and tap-bridges, the network simulator ns-3 offers the possibility to integrate real applications or even hardware into a testbed in which ns-3 emulates the network topology. This eliminates the need to develop separate simulation models. However, there are several differences compared to a model-based discrete event simulation, where applications and network topology run together in the simulation process without real-time constraints. Using ns-3 to build an emulation environment makes it necessary to run in real-time mode, which results in considerable limitations with regard to the achievable throughput and the complexity of the simulated topology. This paper compares the performance that researchers can expect from pure model-based simulations and ns-3-based emulation environments. For this, we evaluate the impact of differently complex network topologies and applications on the simulator throughput in a minimal emulation setup. All measurements are compared with a pure model-based simulation setup. The performance of our setup is measured by the number of possible TCP and UDP flows. With complex network topologies and applications, only a few flows can be handled. In contrast, with simple topologies and applications, the measured throughput of our emulation setup is between 14 Mbps and 120 Mbps. We demonstrate that the achievable throughput additionally depends on ns-3 build profiles and CPU characteristics, highlighting, in particular, the impact of packet throughput as a limiting factor.
Keywords: Real-time systems; Network topology; Emulation; Topology; Performance evaluation; Throughput; Routing protocols; Computational modeling; Complexity theory; Codes

Performance of modern web protocols over satellite links - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (38th International Communications Satellite Systems Conference (ICSSC 2021), 2021)

Performance of the QUIC Transport Protocol over Geostationary Satellite Links - Jahandar Bonab, Saeid; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (40th International Communications Satellite Systems Conference (ICSSC 2023), 2023)
Traditional transport layer protocols like TCP face limitations in high-latency scenarios, such as geostationary satellite communications. The QUIC protocol is a reliable transport protocol designed for secure communication, low-latency connection setup, and evolvability. This study investigates QUIC's advantages in geostationary satellite environments and evaluates the QUIC implementations picoquic and quiche, both with the congestion control algorithms CUBIC and BBR. NetEm is used to introduce specific path characteristics such as data rate and delay. Docker is used to ensure reproducibility, portability, and environmental consistency, facilitating streamlined setup and configuration across different platforms. Assuming that PEPs are not applicable, results demonstrate that QUIC implementations can outperform TCP in connection establishment time and object download time considering a single flow. Utilizing qlog, a logging format for QUIC, aids in-depth analysis of protocol interactions. qlog files are used to show various metrics: time-offset and retransmissions, pacing rate, congestion window size, bytes in flight, round trip times, throughput, and goodput. Results show that picoquic performs better than quiche regardless of the congestion control algorithm. quiche in combination with BBR shows sub-optimal performance which needs further investigatio

POSTER: Revisiting Multipath QUIC Experiments and Comparing them with more recent Multipath TCP Implementations - Schmidt, Tobias; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IEEE Workshop on Local and Metropolitan Area Networks, 2021)
Multipath QUIC is a promising protocol for future multipath communications. One early and often cited Multipath QUIC implementation has been presented by Quentin De Coninck and Olivier Bonaventure in 2017. Their implementation is based on quic-go and results are compared to Multipath TCP Version 0.91, showing performance benefits of Multipath QUIC in various scenarios. In this short paper, we reproduce their experiments and update Multipath TCP to Version 0.92 and later. More recent MPTCP implementations perform much better than Multipath TCP Version 0.91 and thus the performance gain compared to the mentioned Multipath QUIC implementation is not that significant anymore.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Multipath Communication; Multipath QUIC; Multipath TCP

Proto2Testbed: Towards an Integrated Testbed for Evaluating End-to-End Security Protocols in Satellite Constellations - Ottens, Martin; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2025 12th Advanced Satellite Multimedia Systems Conference and the 18th Signal Processing for Space Communications Workshop (ASMS/SPSC), 2025)
There are many approaches to testbed systems in computer networks, but especially when evaluating or developing new security protocols and testing their behavior when used via satellite networks, many challenges remain that no existing system has fully addressed.With Proto2Testbed, we present an approach for a new testbed system that relies on isolated virtual machines. Once a specific testbed is defined, many steps of a typical testbed lifecycle, like testbed setup and experiment coordination, are fully automated. The testbed can be used in multiple ways; one example is the integration of a satellite mega-constellation simulation, thus turning the testbed system into a complete end-to-end emulation environment.Examples are used to demonstrate that Proto2Testbed can be used for various experiments in its current state. The design of future experiments is outlined, which will include a testbed for extensive evaluations of end-to-end security protocol
Keywords: Testbed; Satellite communications; Security protocols; Emulation; Virtualization

QUIC OVER SATELLITE: INTRODUCTION AND PERFORMANCE MEASUREMENTS - Mogildea, Cristian; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (25th Ka and Broadband Communications Conference and the 37th International Communications Satellite Systems Conference, ICSSC 2019, 2019)
Performance Enhancement Proxies and Split TCP are commonly deployed for satellite Internet access in order to improve the performance of TCP. With QUIC and its encrypted transport layer headers, this is not possible anymore. This paper reviews the design principles of QUIC and the impact on satellite Internet access. Based on previous work, we extend the performance evaluation of QUIC over satellite Internet and show that there are performance degradations.
CRIS-Team Scopus Importer:2024-12-16

Satellite internet performance measurements - Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Proceedings of the 2019 International Conference on Networked Systems, NetSys 2019, 2019)
Satellite Internet with geostationary satellites is one way to provide Internet access all over the world. In Europe, there are three major satellite operators. In this paper, their performance is compared with respect to one-way delays, bulk data transfers, and website download times. When one-way delays are measured with UDP packets, the forward link generally shows lower delays than the return link. The bulk data transfers reveal how close actual data rates get to the advertised link rates. Regarding website download times, the web protocols HTTP/1.1, HTTP/2, and QUIC are considered. The results of our TCP measurements show that satellite Internet heavily relies on Performance Enhancement Proxies (PEPs). TCP connections over VPN tunnels cannot benefit from PEPs and therefore result in poor performance. QUIC can perform better than TCP tunneled in VPNs, but performs worse than TCP connections optimized by PEPs. One operator generally shows more stable performance regarding delays, data rates and page load times.
CRIS-Team Scopus Importer:2019-11-01
Keywords: HTTP; Performance Measurements; QUIC; Satellite Internet; TCP; UDP

TCP CUBIC with HyStart: Congestion Control for Satellite Communication in OMNeT++ INET - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2024 IEEE 29th Asia Pacific Conference on Communications (APCC), 2024)
In the context of satellite communication, unique challenges arise, such as long delay links that can impact the network performance also at the Transport Layer. With regard to the Transmission Control Protocol (TCP), congestion control plays a crucial role in managing network traffic and ensuring efficient data transmission over the Internet. This paper wants to give an overview of how TCP congestion control mechanisms adapt to mitigate the effects of long link delays, highlighting the importance of optimizing protocols for these specific environments. Within this context, where signals travel extended distances, traditional TCP algorithms designed for terrestrial networks with relatively low latency, may struggle to maintain optimal performance. As a result, specialized congestion control algorithms, like TCP CUBIC, can be employed to address these challenges. Through the integration of TCP CUBIC with HyStart within a simulation framework based on OMNeT++ and INET, this study sheds light on the importance of tailoring congestion control strategies to suit specific network environments including satellite communicatio

Topology Simulation for Aeronautical Communication Protocols with ns-3 and DCE - Lehmann, Andreas; Kreuzer, Matthias; Deutschmann, Jörg; Berold, Ulrich; Huber, Johannes (Proceedings of the Workshop on ns-3, 2016)

Towards a 5G Satellite Communication Framework for V2X - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Würzburg Workshop on Modeling, Analysis and Simulation of Next-Generation Communication Networks 2023 (WueWoWAS’23), 2023)
In recent years, satellite communication has been expanding its field of application in the world of computer networks. This paper aims to provide an overview of how a typical scenario involving 5G Non-Terrestrial Networks (NTNs) for vehicle to everything (V2X) applications is characterized. In particular, a first implementation of a system that integrates them together will be described. Such a framework will later be used to evaluate the performance of applications such as Vehicle Monitoring (VM), Remote Driving (RD), Voice Over IP (VoIP), and others. Different configuration scenarios such as Low Earth Orbit and Geostationary Orbit will be considered.<br

Towards a comparative study of application performance in an automotive environment with 5G non-terrestrial networks - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IET, 2024)
Non-Terrestrial Networks (NTNs), and in particular satellite networks, are emerging as a promising solution to extend the coverage and capacity of wireless networks beyond the limitations of terrestrial infrastructure. One such technology that has been heavily researched in recent years is 5G, which promises to improve the way we communicate by providing high data rates, machine-to-machine communications and ultra-reliable low-latency communications. In particular, the automotive industry is expected to greatly benefit from 5G, as it can enable a range of advanced applications such as autonomous driving, vehicle-to-vehicle (V2V) and vehicle- to-infrastructure (V2I) communications. However, the deployment of 5G in vehicular environments is still facing significant challenges, such as ensuring reliable and secure communication, providing efficient mobility management, and optimizing the use of radio resources. In this context, this paper provides an overview of automotive applications such as Voice over IP (VoIP), Vehicle Monitoring (based on UDP) and a file bulk transfer (based on TCP) over a Geostationary and Low Earth Orbit link, highlighting the key issues and potential solutions to enable the seamless integration of vehicular communications into these emerging network